CA Foundation Question > If log (2a - 3b) = log a - log b, then a =a)3...

If log (2a - 3b) = log a - log b, then a =

- a)3b
^{2 }/ 2b-1 - b)3b
^{ }/ 2b-1 - c)b
^{2 }/ 2b+1 - d)3b
^{2 }/ 2b+1

Correct answer is option 'A'. Can you explain this answer?

1 Crore+ students have signed up on EduRev. Have you? |

If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer?

2a-3b=a/b

2a=a/b+3b

2a=a+3b2/b

2ab=a+3b2

2ab-a=3b2

a(2b-1)=3b2

a=3b2/2b-1

answer=a)

2a=a/b+3b

2a=a+3b2/b

2ab=a+3b2

2ab-a=3b2

a(2b-1)=3b2

a=3b2/2b-1

answer=a)

View courses related to this question | Explore CA Foundation courses |

Explore CA Foundation courses View courses related to this question |

Question Description

If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? for CA Foundation 2023 is part of CA Foundation preparation. The Question and answers have been prepared according to the CA Foundation exam syllabus. Information about If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? covers all topics & solutions for CA Foundation 2023 Exam. Find important definitions, questions, meanings, examples, exercises and tests below for If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer?.

If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? for CA Foundation 2023 is part of CA Foundation preparation. The Question and answers have been prepared according to the CA Foundation exam syllabus. Information about If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? covers all topics & solutions for CA Foundation 2023 Exam. Find important definitions, questions, meanings, examples, exercises and tests below for If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer?.

Solutions for If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? in English & in Hindi are available as part of our courses for CA Foundation.
Download more important topics, notes, lectures and mock test series for CA Foundation Exam by signing up for free.

Here you can find the meaning of If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? defined & explained in the simplest way possible. Besides giving the explanation of
If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer?, a detailed solution for If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? has been provided alongside types of If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? theory, EduRev gives you an
ample number of questions to practice If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? tests, examples and also practice CA Foundation tests.

This discussion on If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? is done on EduRev Study Group by CA Foundation Students. The Questions and
Answers of If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? are solved by group of students and teacher of CA Foundation, which is also the largest student
community of CA Foundation. If the answer is not available please wait for a while and a community member will probably answer this
soon. You can study other questions, MCQs, videos and tests for CA Foundation on EduRev and even discuss your questions like
If log (2a - 3b) = log a - log b, then a =a)3b2 / 2b-1b)3b/ 2b-1c)b2 / 2b+1d)3b2 / 2b+1Correct answer is option 'A'. Can you explain this answer? over here on EduRev! Apart from being the largest CA Foundation community, EduRev has the largest solved
Question bank for CA Foundation.